Compressible Fanno flows in micro-channels: An enhanced quasi-2D numerical model for turbulent flows. (February 2020) - Cavazzuti, Marco; Corticelli, Mauro A.; Karayiannis, Tassos G.
Abstract: Fanno theory provides an analytical model for one-dimensional confined viscous compressible flows. The model holds under the assumptions of adiabatic flow and constant cross-section channel. From theory, the differential of every flow-related quantity is expressed as a function of Mach number and friction factor. One-dimensional flow numerical models can be derived by discretizing Fanno equations. However, theory does not assess how to evaluate friction, while the model works properly only if friction is estimated correctly. Compressibility and turbulence act by deforming the velocity profile making it flatter. Assuming the friction factor function of the Reynolds number alone, in line with incompressible flow theory, is thus not correct. Better correlations should include the Mach number to address compressibility effects. Here, the impact of turbulence and compressibility on the velocity profiles in a micro-channel is analysed by means of CFD simulations. Friction factor correlations are deduced for turbulent micro-flows. The impact of the velocity profile on other quantities, such as dynamic pressure and bulk temperature, needed for the numerical model operation, is also evaluated. Additional correlations for these quantities overcome the instrinsic limits of the one-dimensional model, necessarily unaware of local velocity profiles, in a quasi-2D fashion significantly improving its predicting capabilities. Highlights: An enhanced model for solving turbulent Fanno flow in micro-channels is presented. Compressibility effects are investigated and addressed in a quasi-2D fashion. A detailed analysis of compressible velocity and temperature profiles is made. Correlations for dynamic pressure, bulk temperature, and friction are derived. The improved prediction capability of the numerical model is assessed.